FACULTYS AND STUDENTS PERCEPTIONS AND ADJUSTMENTS TO ONLINE LEARNING IN THE ERA OF COVID-19 IN UNIVERSITIES IN THE NORTH EAST, NIGERIA - odaudu, sunday; Jutum, Joel; Adejo-odaudu, Victoria (African Journal of Behavioural and Scale Development Research, 2022)
The COVID19 pandemic has had a calamitous effect on the world-wide economy and particularly on education in developing countries. The education system world over was faced with a crises which created uncertainty among critical stakeholders in the education industry and posed a threat to the education system performance and sustainability. Transitioning to remote work and learning environment has remained one of the nagging issues in our education development trajectory in view of cost of data and bandwidths availability. However, efforts are being made to help faculties and students adjust to online learning mode. This study therefore, focuses on faculties and students perceptions and adjustments to online learning in the period of COVID19 in universities in North East Nigeria. Three questions were highlighted to define a scope for the study while one hypothesis was formulated to be tested at 0.05 significance level. The major instrument for data collection is a questionnaire titled “faculty and students adjustment to online learning questionnaire” (FSPAOQ) distributed through online using Google Form. The population of the study involved of 16,020 faculties and students of faculty of education in the North East Nigeria while 583 respondents constitutes the sample size. The data analysis methodologies employed includes descriptive statistics of mean and standard deviation, percentages and frequency sufficient to answers the research questions as well as inferential statistics using Multiple Regression Analysis for hypothesis testing at 0.05 significance level. Necessary recommendations were made for planning education and for policy on the basis of the findings in this study.